Facets of the hospitality philosophy: filotexnia - Bortnykov, Y.; Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович; Chuieva, I.; Konoh, O.; Konoh, A. (My University, 2021)
Considers the possibility of establishing the Hospitality Philosophy as an independent field of philosophical knowledge. Theoretical basis. Theoretical basis for this issue is the numerous philosophical researches on the topic of hospitality (anthropological, phenomenological, ethical, social-philosophical etc.) and the analysis of its essence and paradigmatic antinomy in the historicalphilosophical way. Scientific novelty. The article attempts to revitalise the notion of philotechnics (φιλοτεχνία) as 'the art of taking care of the guest's welfare' as a possible basic concept of contemporary philosophy of hospitality, which is able to reflect its nature most concisely, including its utilitarian and extra-utilitarian functions – not only a high service level, but also a “humane” attitude towards the guest. Findings. It has been summarized that modern hospitality as a specific human activity needs its own philosophy, which would comprehensively analyze the concept, study the facets and forms of its manifestations, define the worldview paradigm, form a methodology and be able to lead to an understanding of the goals of hospitality, to orient modern hospitality models to achieve certain and clear quality indicators while respecting historically verified value constants.
Keywords: hospitality; philosophy of hospitality; philotechnics